504 EVALUATION OF AN ORAL HEALTH PROMOTION PROGRAM IN A REMOTE FIRST NATIONS COMMUNITY. (1st January 2005) - Ho, J.; Lai, Y. H.; Benton, D.; Duffy, D.; Harrison, R.; Macnab, A. J.
Abstract : Background: Poor oral hygiene is associated with an increased risk of diabetes, coronary artery disease and premature labor; all major issues for First Nations populations. For over 3 years our university has shared a collaborative health prevention and education partnership with a remote Tsimshian community in Northern British Columbia promoting oral health amongst their children and providing unique educational opportunities for pediatric residents. Method: After an extensive dialogue between the Band Council and our Residency Training Committee, a school-based program centered on brushing, flossing, and topical fluoride began. Pre-intervention assessment and training were done jointly by the departments of Dentistry and Pediatrics. Residents and a faculty supervisor stay in the community every 2 months to contribute ongoing support, age-appropriate educational modules for the children, and collaborative health care services (acute and preventive) with the Health Director and the local nursing station. Multidisciplinary evaluation is ongoing and includes oral, general health, community awareness and involvement and educational parameters. Results: 80 children (100% of those of school age) were enrolled. Initially the majority of children had evidence of poor oral health, and knowledge and practices were limited. Less than 20% of the children were decay free, and the mean decay missing filled score (DMFS) for preK children was 9.9 (SD 12.1); for school aged children (k–12) the DMFS score was 5.7 (SD 6.2). One year later, 41% of the children enrolled in the study have no new cavities. Currently, all the children in the community remain enrolled in the program. The results are seen as significant by the community. 45 pediatric trainees and 18 faculty members have spent time in the community; our trainees evaluate their involvement as an educational highlight in their training; and the program has received awards from Aboriginal and University agencies. Conclusion: The 'Brighter Smiles program' has synergistically combined the culture and knowledge of a vibrant First Nation's community with those of a University Residency program committed to advocacy for child health and innovative resident education. Key attitudes have changed for both groups and a measurable improvement in oral health has occurred.